Evaluation of bioavailability of nitric oxide in coronary circulation by direct measurement of plasma nitric oxide concentration - Neishi, Yoji (National Academy of Sciences, 2005)
Although bioavailability of NO in the coronary circulation is commonly evaluated by acetylcholine (ACh)-induced vasodilation, a change in plasma NO concentration and its relation to the flow response after injection of ACh are still unknown. Thus, we directly measured the concentration of NO in the coronary sinus by using a catheter-type NO sensor for coronary sinus. An NO-sensitive sensor was located and fixed in a 4-Fr catheter with a soft tip for protection of vascular wall. After calibration with an NO-saturated pure water, the catheter-type NO sensor was located in the coronary sinus in anesthetized dogs. The coronary flow velocity (CFV) was measured with a Doppler guide wire. Intracoronary injection of ACh (0.4 and 1.0 μg/kg) increased plasma NO concentration in a dose-dependent manner (3–10 nM). Although ACh increased CFV by 95%, there was no significant difference between the two ACh doses. After ACh, the peak value of plasma NO concentration was observed significantly later than CFV. N(G)-methyl-l-arginine (NO synthase inhibitor) decreased basal NO concentration by 3 nM and suppressed the ACh-induced NO synthesis with no significant change in average peak velocity. We conclude that production of NO in the coronary circulation can be evaluated in the coronary sinus. Although ACh increases both CFV and NO concentration, CFV dose not reflect NO concentration in terms of magnitude and time course. Direct measurement of plasma NO concentration by the catheter-type NO sensor is useful to evaluate bioavailability of NO in the coronary circulation.